The Thyroid Hormone Receptors as Modulators of Skin Proliferation and Inflammation - Contreras Jurado, Silvia Constanza; García Serrano, Laura; Gómez Ferrería, María Ana; Costa, Clotilde; Paramio, Jesus M.; Aranda, Ana (My University, 2021)
We have analyzed the role of the thyroid hormone receptors (TRs) in epidermal homeostasis. Reduced keratinocyte prolifer ation is found in interfollicular epidermis of mice lacking the thyroid hormone binding isoforms TR 1 and TR (KO mice). Similar results were obtained in hypothyroid animals, showing the important role of the liganded TRs in epidermal prolifera tion. In addition, KO and hypothyroid animals display de creased hyperplasia in response to 12-O-tetradecanolyphorbol 13-acetate. Both receptor isoforms play overlapping functional roles in the skin because mice lacking individually TR 1 or TR also present a proliferative defect but not as marked as that found in double KO mice. Defective proliferation in KO mice is associated with reduction of cyclin D1 expression and up-regu lation of the cyclin-dependent kinase inhibitors p19 and p27. Paradoxically, ERK and AKT activity and expression of down stream targets, such as AP-1 components, are increased in KO mice. Increased p65/NF- B and STAT3 phosphorylation and, as a consequence, augmented expression of chemokines and proinflammatory cytokines is also found in these animals. These results show that thyroid hormones and their receptors are important mediators of skin proliferation and demonstrate that TRs act as endogenous inhibitors of skin inflammation, most likely due to interference with AP-1, NF- B, and STAT3 activation.